2020
DOI: 10.5534/wjmh.180066
|View full text |Cite
|
Sign up to set email alerts
|

Microtubular Dysfunction and Male Infertility

Abstract: Microtubules are the prime component of the cytoskeleton along with microfilaments. Being vital for organelle transport and cellular divisions during spermatogenesis and sperm motility process, microtubules ascertain functional capacity of sperm. Also, microtubule based structures such as axoneme and manchette are crucial for sperm head and tail formation. This review (a) presents a concise, yet detailed structural overview of the microtubules, (b) analyses the role of microtubule structures in various male re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 97 publications
0
26
0
1
Order By: Relevance
“…Furthermore, our research listed the top 10 ranked GO terms that showed a significant correlation of guanyl‐nucleotide exchange factor activity (Figure 4), and KEGG analysis indicated that regulation of the actin cytoskeleton was the most enriched pathway relevant to spermatogenesis (Figure 5). During the process of proliferation and differentiation of the spermatogenic cells, cytoskeleton architecture undergoes a major reshaping change and the vital cytoskeletal components, including microfilaments, microtubules and intermediate filaments, play a major role in spermatogenesis (Gunes et al., 2020; Kaneko et al., 2019; Liu et al., 2018). Abnormalities in cytoskeleton rearrangement process can affect the differentiation of spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our research listed the top 10 ranked GO terms that showed a significant correlation of guanyl‐nucleotide exchange factor activity (Figure 4), and KEGG analysis indicated that regulation of the actin cytoskeleton was the most enriched pathway relevant to spermatogenesis (Figure 5). During the process of proliferation and differentiation of the spermatogenic cells, cytoskeleton architecture undergoes a major reshaping change and the vital cytoskeletal components, including microfilaments, microtubules and intermediate filaments, play a major role in spermatogenesis (Gunes et al., 2020; Kaneko et al., 2019; Liu et al., 2018). Abnormalities in cytoskeleton rearrangement process can affect the differentiation of spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Primary ciliary dyskinesia (PCD) is a heterogeneous and multisystemic disorder characterized by structural and/or functional abnormalities of the motile cilia. It is a rare autosomal recessive disease, whose prevalence varies from 1:10,000 to 1:20,000 people worldwide (Gunes et al, 2018). The clinical features include chronic sinusitis, bronchiectasis, rhinitis, rhinorrhea, and chronic cough, largely due to a defective mucociliar clearance of the respiratory tract (Barbato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is common in male patients with PCD/Kartagener syndrome. It is mainly ascribed to flagella abnormalities, leading to sperm immotility (Gunes et al, 2018). Transmission electron microscopy (TEM) analysis has documented a number of ultrastructural defects at the sperm level, such as dynein arm deficiency (Kordus et al, 2008), abnormal connecting pieces, shortened mid pieces with attenuated mitochondria sheaths, poorly developed annulus, abnormal outer dense fibers, axonema missing the two central microtubules (Yokota et al, 1993;McLachlan et al, 2012), or dysplasia of the fibrous sheath (Moretti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in either the formation of the nuclear head or the flagellum can 226 result in reciprocal abnormalities in the other process. This has been shown to be a result of disruptions in 227 intra-manchette transportation of proteins essential for spermatogenesis in mammals [23,29]. In fact, over 228 a dozen genes in mammals have recently been identified to be involved in intra-manchette transportation 229 that perturb both the remodeling of the nuclear head as well as the formation of the flagellum [30].…”
mentioning
confidence: 99%
“…In fact, over 228 a dozen genes in mammals have recently been identified to be involved in intra-manchette transportation 229 that perturb both the remodeling of the nuclear head as well as the formation of the flagellum [30]. While 230 there is still a lot unknown about the function of the manchette, it is suggested to be very similar to 231 intraflagellar transportation [23]. Interestingly, we identify here a very similar structure in Drosophila 232 ( Figure 4F and 5E,F, white arrow) that has previously been referred to as the dense complex [26,31,32] 233 and has been reported to be involved in the reshaping of the nuclear head [26,33,34].…”
mentioning
confidence: 99%